2015
DOI: 10.1038/ncomms10001
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assessment of somatic mutation detection in cancer using whole-genome sequencing

Abstract: As whole-genome sequencing for cancer genome analysis becomes a clinical tool, a full understanding of the variables affecting sequencing analysis output is required. Here using tumour-normal sample pairs from two different types of cancer, chronic lymphocytic leukaemia and medulloblastoma, we conduct a benchmarking exercise within the context of the International Cancer Genome Consortium. We compare sequencing methods, analysis pipelines and validation methods. We show that using PCR-free methods and increasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
265
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 276 publications
(276 citation statements)
references
References 39 publications
9
265
1
Order By: Relevance
“…Each group analyzed the data separately and reported results back to a central analysis team. Some centers expressed interest in publishing their findings, 3 which at the time raised some concern that the benchmarking activity might be better categorized as research.…”
Section: This Paper Was Composed By Members Of the Ethics And Policymentioning
confidence: 99%
“…Each group analyzed the data separately and reported results back to a central analysis team. Some centers expressed interest in publishing their findings, 3 which at the time raised some concern that the benchmarking activity might be better categorized as research.…”
Section: This Paper Was Composed By Members Of the Ethics And Policymentioning
confidence: 99%
“…A data analysis pipeline sequentially applies a suite of programs with adjustable parameters, and different combinations of programs and thresholds may produce diverse results. For example, a recent study showed that one pipeline produces more than 4-fold more single-nucleotide variants (SNVs) from the same dataset than other pipelines (1). Published studies compared different pipelines that employ open source and commercial software, and most of them analyze NGS data generated by using Illumina's platform (1,15,39).…”
Section: Identification Of Somatic Mutations From Wes Datamentioning
confidence: 99%
“…For example, a recent study showed that one pipeline produces more than 4-fold more single-nucleotide variants (SNVs) from the same dataset than other pipelines (1). Published studies compared different pipelines that employ open source and commercial software, and most of them analyze NGS data generated by using Illumina's platform (1,15,39). There is no publicly available datasets applicable to WES of clinical samples of cancer tissues collected at single institute, which are sequenced at sufficient depths using the Ion Proton System.…”
Section: Identification Of Somatic Mutations From Wes Datamentioning
confidence: 99%
“…Such a study would provide a decisive explanation about the genetic effects of radiation in humans. However, currently, whole genome sequencing techniques are reasonably effective at detecting base-change mutations, but are not yet good enough to detect copy number changes (insertions and deletions) (38). Currently, one of the best methods to detect deletion mutations would be to use the array-based comparative genomic hybridization (CGH) method (see Fig.…”
Section: A New Approach Utilizing Genome Informationmentioning
confidence: 99%